The effectiveness of company policies and standard operating procedures to curb internal fraud and wrongdoings: a case study of Celcom Axiata Berhad / Rafidah Osman - Osman, Rafidah (2013)
The purpose of this study is to explore the effectiveness of escalating company policies and standard operating procedures at Celcom Axiata Berhad as well as the possible reason behind the violation of the clause in the documents. In spite of, this study also provide ample evidence of the case of internal fraud and employee's wrongdoings at Celcom Axiata Berhad from January 2012 until September 2013.Thus, the emphasis in the research is to provide fundamental discussing about internal fraud and wrongdoings cases and advantage of establishing and maintaining a set of company policy and standard operating procedures as a reference document to set limit, maintain control and resolved dispute among employees and other interested parties to curb internal fraud and wrongdoings among employees. The aim of this study is (i) to ascertain whether Celcom Axiata Berhad has specific policies and standard operating procedures to curb internal fraud; (ii) to determine whether Celcom Axiata Berhad’s policies and standard operating procedures on internal frauds are successful in preventing fraud cases; and (iii) to assess the level of awareness and comprehension among employees on the existence of relevant company policies and standard operating procedures on internal fraud prevention; and (iv) to examine the opportunity and rationalization for internal fraud in Celcom Axiata Berhad. This study adopted content analysis of file and company documents as the instruments for data collection. The cases selected in this study will be based on actual cases that had been investigated and enforcement was discharged. A total of seven cases were involved in this study. All the case studies involved with internal fraud and wrongdoings at Celcom Axiata Berhad reported in January 2012 until September 2013. The name of the staff involved is not disclosed due to private and confidential information. The case files were obtained from department of Fraud Prevention and Investigation under Facilities Division, Celcom Axiata Berhad. However for company policy and standard operating procedures were retrieved from Document Control System by accessing the company intranet, also known as Bluenet. The findings from this study demonstrates that the internal fraud involving employee’s misconduct and wrongdoing might be reduces if documented policies and standard operating procedures are now in place for all major aspects of the company’s business, workable, well establish and maintain to ensure that they remain effective.